PANDANGAN ISLAM TERHADAP PERHITUNGAN WETON DALAM PERKAWINAN - Faruq, Ahmad (Irtifaq, 2019)
Marriage is the most important institution for the Islamic peopleespecially to form a family that is sakinah, mawaddah and rahmah. SomeJavanese people use days based on Wethon, good days, and so on. Since thecalendar period, which is a blend of native and Hindu Javanese with the yearname Saka (saka calendar) was used by the Javanese people until 1633 AD At thetime of Sultan Agung Hanyakrakusuma, he reigned. The famous king of Mataramwho obeyed Islam changed the calendar on Java in a revolutionary manner. Atthat time the Saka calendar had been running until the end of 1554. The figure of1554 was continued in the Sultan Agung calendar in 1955, even though the basisof the calculations was completely different. Petungan Jawi has existed for a longtime and is a record of the ancestors based on good and bad experiences recordedon primbon. The word primbon is derived from the word lush store or deposit, sothe primbon contains various calculations by a generation derived next generation.Most Javanese have the confidence to use petungan to do things like marriage,harvesting, building houses and others. In petungan there is a name called wetonin every weton which has its own value.Keywords: Marriage, Petungan day, Islam